A critical assessment of the synthesis and biological activity of p53/human double minute 2‐stapled peptide inhibitors. (6th July 2017) - Wallbrecher, Rike; Chène, Patrick; Ruetz, Stephan; Stachyra, Therese; Vorherr, Thomas; Brock, Roland
Abstract : Background and Purpose: Helix stapling enhances the activity of peptides that interact with a target protein in a helical conformation. These staples are also supposed to change the pharmacokinetics of the molecules and promote cytoplasmic targeting. We assessed the extent to which the pharmacokinetic characteristics are a function of the staple for a peptide inhibiting the interaction of p53 with the human double minute 2 (Hdm2) protein and differ from those of the standard cationic cell‐penetrating peptide nona‐arginine. Experimental Approach: Stapled peptides and linear counterparts were synthesized in free and fluorescently labelled forms. Activity was determined in biochemical time‐resolved Förster resonance energy transfer experiments and cellular high‐content assays. Cellular uptake and intracellular trafficking were visualized by confocal microscopy. Key Results: Peptides showed sub‐nanomolar potency. For short‐time incubation, uptake efficiencies for the stapled and linear peptides were similar and both were taken up less efficiently than nona‐arginine. Only for SJSA‐1 cells expressing the Hdm2 target protein, the stapled peptides showed an enhanced cytoplasmic and nuclear accumulation after long‐term incubation. This was also observed for the linear counterparts, albeit to a lesser degree. For HeLa cells, which lack target expression, no such accumulation was observed. Conclusion and Implications: Cytosolic and nuclear accumulation was not an intrinsic property of the stapled peptide, but resulted from capture by the target Hdm2 after endo‐lysosomal release. Considering the rather poor uptake of stapled peptides, further development should focus on increasing the efficiency of uptake of these peptides.